2021
DOI: 10.7150/jca.49673
|View full text |Cite
|
Sign up to set email alerts
|

Histologic Lymph Nodes Regression after Preoperative Chemotherapy as Prognostic Factor in Non-metastatic Advanced Gastric Adenocarcinoma

Abstract: Background: The study aims to evaluate the lymph node (LN) response to preoperative chemotherapy and its impact on long-term outcomes in advanced gastric cancer (AGC). Methods: Histological specimens retrieved at gastrectomy from patients who received preoperative chemotherapy were evaluated. LN regression was graded by the adapted tumor regression grading system proposed by Becker. Patients were classified as node-negative (lnNEG) in the case of all negative LN without evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 37 publications
0
9
0
4
Order By: Relevance
“…Histologic downstage of cN+ status results in prolonged survival [107,108]. Moreover, regression of LN status is more significant than regression of the primary tumour in predicting GC recurrence [107].…”
Section: Nodal Regression Gradementioning
confidence: 99%
See 1 more Smart Citation
“…Histologic downstage of cN+ status results in prolonged survival [107,108]. Moreover, regression of LN status is more significant than regression of the primary tumour in predicting GC recurrence [107].…”
Section: Nodal Regression Gradementioning
confidence: 99%
“…Histologic downstage of cN+ status results in prolonged survival [107,108]. Moreover, regression of LN status is more significant than regression of the primary tumour in predicting GC recurrence [107]. Additionally, LN regression, regardless of the percent of tumour cells in the primary site, independently influences the survival in patients who underwent NAC [109].…”
Section: Nodal Regression Gradementioning
confidence: 99%
“…Other studies have similarly concluded that survival is improved in patients who have lymph node responses to chemotherapy, despite poor response to chemotherapy in primary tumors [8,[13][14][15]. It has been reported that the survival of patients with Mandard score (3-5) in the ypN0 group was similar to that of patients with Mandard score (1-2) [15].…”
Section: Discussionmentioning
confidence: 88%
“…Other studies have similarly concluded that survival is improved in patients who have lymph node responses to chemotherapy, despite poor response to chemotherapy in primary tumors [8,[13][14][15]. It has been reported that the survival of patients with Mandard score (3-5) in the ypN0 group was similar to that of patients with Mandard score (1-2) [15]. Our study further compared median survival in different ypN stage subgroups of patients with Mandard Radiography plays an important role in evaluating tumor regression after chemotherapy [20][21][22].…”
Section: Discussionmentioning
confidence: 94%
“…The three-tier system is the most investigated classification in both upper 6,[8][9][10]12,13,15,17,30 and lower gastrointestinal tumours, 2,4,7,16 where node-negative patients with (ypNÀReg+) and without response (ypNÀRegÀ) are compared with ypN+ patients. In our cohorts, we observed that patients with ypNÀReg+ have at least similar OS to and even better DFS than those with never positive nodes (ypNÀRegÀ).…”
Section: Discussionmentioning
confidence: 99%